FAKTOR KESULITAN BELAJAR MATA KULIAH RENANG MAHASISWA PENKESREK FAKULTAS ILMU OLAHRAGA UNESA - muyasaroh, laili; pramono, made (Jurnal Kesehatan Olahraga, 2019)
This research was conducted due to it was deemed necessary to add scientific knowledge, the purpose of this research was to find out what factors were the difficulties of Penkesrek undergraduate students who had not graduated yet in taking swimming courses. Factor of mastering motion techniques and factor of physiognomy (physiology and anatomy). In this research there were limitations because of the existence of financial factors. In this research, the sample only uses Penkesrek Undergraduate students who are taking swimming courses. The method used in this research is a survey method with data collection techniques using instrument interviews. The sample of this research was 30 students. The researcher took 10 of them randomly selected. Based on research conducted with interview techniques on test participants who had difficulty showing results with details of butterfly style about 26 people, backstroke about 18 people, breaststroke about 7 people, freestyle about 5 people.Factors in mastering motion techniques and physiological and anatomical factors are two factors found. Keywords: Physical Freshness, Futsal Extracurricular